2016
DOI: 10.1002/hed.24579
|View full text |Cite
|
Sign up to set email alerts
|

High prevalence of self‐reported shoulder complaints after thyroid carcinoma surgery

Abstract: Shoulder complaints represent and underestimated problem and are reported by many patients who had surgery for thyroid carcinoma. Information provision to the patient should be improved, shoulder complaints should be registered, and additional care should be provided after thyroid carcinoma surgery to improve QOL. © 2016 Wiley Periodicals, Inc. Head Neck 39: 260-268, 2017.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 26 publications
(51 reference statements)
1
9
0
Order By: Relevance
“…Interestingly, a considerable number of patients said they felt there should be more items on shoulder functioning which was why we added another item on this issue. This is in line with a recent study (Roerink et al 2017) which found that more than half of the thyroid cancer survivors suffer from shoulder problems.…”
Section: Discussionsupporting
confidence: 93%
“…Interestingly, a considerable number of patients said they felt there should be more items on shoulder functioning which was why we added another item on this issue. This is in line with a recent study (Roerink et al 2017) which found that more than half of the thyroid cancer survivors suffer from shoulder problems.…”
Section: Discussionsupporting
confidence: 93%
“…The negative HRQOL repercussions of neck dissection was highlighted, in particular shoulder complaints, loss of neck sensation, swallowing discomfort, and reduced chewing ability. 17 , 20 , 22 , 33 Almeida et al 20 found patients who had level II to VI neck dissections to have significantly worse chewing and shoulder scores relative to QOL, in comparison to those who underwent level VI alone. Lee et al 22 reported the potential benefit from robotic surgery in patients undergoing neck dissection.…”
Section: Resultsmentioning
confidence: 99%
“…Spinal accessory nerve injury is a common complication of neck dissection and leads to reduced shoulder mobility and pain (33). Other nerval complications include impaired arm mobility (brachial plexus) and facial muscle mobility (facial nerve).…”
Section: Special Aspects and Late Term Functional Impairments In Hncmentioning
confidence: 99%